Otto Dix e a cultura de Weimar: arte, modernidade e guerra - Soler, Victor Amadeu (2020)
The objective of this master's essay is to take an analytical look at some of Otto Dix's paintings (1891-1961), making evident its conjuncture in the Weimar Republic (1919-1933) and the idea of a critique of a postwar German society. Furthermore, this academic work aims to present, what forms reveal themselves in Dix's paintings, the conflicts, the cultural values, the ambiguities of a Germany that, at a time, used to dialogue with a notion of Kultur linked to the idea of community, of cultural unity that seemed absent and, at another one, a notion of Zivilisation, which was becoming dominant in that temporality. Through the paintings of Otto Dix, as they are exhibited, I seek to establish possible connections between art and the conflictive conjuncture experienced by the period's German society, considering that the world affects art as much as art affects the world. Dix's artistic work is not just an “image” of Weimar, but a critical product of a sociocultural universe - the bourgeois modernity. It was in Weimar's Germany that Otto Dix and his paintings took the main stage, that became evident the influxes and the convulsions of this society on his work, although it is not intended to assume a sociological view of art, since the focus of this work is not the society itself, but its representation through Dix's works